Caracterización de la producción de zarzamora, el caso del municipio de Tacámbaro, Michoacán - Gutiérrez Cervantes, Ariadna (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
In recent years, our country has led the world in blackberry production, a result largely achieved by the fruit produced in Michoacán, the state with the highest production volume nationwide. In Michoacán, this activity began in the Los Reyes area and its surroundings; however, it quickly spread to other municipalities with favorable climate and soil conditions. The arrival of blackberries in the fields of Tacámbaro brought new challenges for agricultural producers, who adopted the activity in just a few years, which has seen significant growth. Currently, blackberries are the second most important agricultural product in the municipality, due to the product's widespread acceptance in international markets and the dynamics generated in the municipality itself since the introduction of the activity. This characterization describes the processes and factors that have influenced the behavior of blackberry production in the municipality of Tacámbaro, the identification of the actors involved and the current panorama of the activity, derived from the information provided by producers, concluding with an analysis of strengths, opportunities, weaknesses and threats of the sector in the municipality, and problem-solving proposals that can serve as a guide to decision-makers at the municipal level.

Nuestro país ha liderado en los últimos años la producción mundial de zarzamora, resultado conseguido en gran medida por la fruta producida en Michoacán, que es el estado con mayor volumen de producción a nivel nacional. En Michoacán, esta actividad se inició en la zona de Los Reyes y sus alrededores, sin embargo, rápidamente se trasladó a otros municipios con condiciones propicias en clima y suelos. La llegada de la zarzamora a los campos de Tacámbaro, trajo nuevos retos para los productores agrícolas, que en pocos años adoptaron la actividad, misma que ha tenido un crecimiento significativo; actualmente la zarzamora es el segundo producto agrícola más importante del municipio, derivado de la gran aceptación del producto en mercados internacionales y las dinámicas que se han generado en el mismo municipio a partir de la inserción de la actividad. En esta caracterización se describen los procesos y factores que han incidido en el comportamiento de la producción de zarzamora en el municipio de Tacámbaro, la identificación de los actores involucrados y el panorama actual de la actividad, derivado de la información proporcionada por productores, finalizando con un análisis de fortalezas, oportunidades, debilidades y amenazas del sector en el municipio, y propuestas de resolución de problemas que pueden servir de guía a los tomadores de decisiones en el ámbito municipal.
Facultad de Economía Vasco de Quiroga. Maestría en Asuntos Públicos para la Sustentabilidad
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2025-1145; Zarzamora; Exportación; Valor de la producción; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19415